2012
DOI: 10.1103/physrevlett.108.173401
|View full text |Cite
|
Sign up to set email alerts
|

Angular-resolved Photoelectron Spectroscopy of Superatom Orbitals of Fullerenes

Abstract: Photoelectron angular distributions from both C(60) and C(70) were recorded for low laser intensity femtosecond and picosecond pulses. Rich structure is seen for electron kinetic energies that lie below the photon energy. Strong, broad peaks are observed for photoelectron energies corresponding to single-photon ionization of so-called superatom molecular orbitals (SAMOs). The very simple angular distributions measured for these peaks, the close similarity of the spectra observed from C(60) and C(70), and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 18 publications
7
67
0
Order By: Relevance
“…[26,27,28]. Similar calculations have also been performed by employing Linearized Time-Dependent DFT (L-TDDFT), in which free plane waves for the outgoing wave functions are considered in the calculation of the anisotropy parameter β 2 , for various laser frequencies [23]. However, free plane waves might constitute an oversimplication which can significantly impact β 2 , see discussion in Section 5.3.2 and [29].…”
Section: Introductionmentioning
confidence: 99%
“…[26,27,28]. Similar calculations have also been performed by employing Linearized Time-Dependent DFT (L-TDDFT), in which free plane waves for the outgoing wave functions are considered in the calculation of the anisotropy parameter β 2 , for various laser frequencies [23]. However, free plane waves might constitute an oversimplication which can significantly impact β 2 , see discussion in Section 5.3.2 and [29].…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes are nanometer-size systems with interesting physical properties, including high polarizability [32], superatomic molecular orbitals [33,34] with macroatom behavior [35], large photoionization cross sections [36,37], and efficient high-harmonic generation [38][39][40]. The ionization and fragmentation of C 60 have been investigated extensively in the past (see, e.g., [35,[41][42][43][44][45][46][47]).…”
mentioning
confidence: 99%
“…The details of the experimental techniques have been provided in previous publications [5,8,9] and will be only briefly described here. The original studies that reported the excitation and subsequent single-photon ionization of Rydberg states in C 60 were carried out with a combined linear time-of-flight photoelectron spectrometer and a time-of-flight mass spectrometer (MS) [5,10].…”
Section: Methodsmentioning
confidence: 99%
“…The emphasis was placed on the determination of the binding energies of the higher lying members of the Rydberg series that were well resolved using 800 nm laser pulses with 1.5 ps duration. In more recent studies, the time-of-flight photoelectron spectrometer was replaced by a velocity map imaging (VMI) spectrometer, illustrated in figure 2 [8,9]. This incorporates a position-sensitive detector consisting of a set of multichannel plates followed by a phosphor screen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation